On Convergence Theorems for Generalized Alpha Nonexpansive Mappings in Banach Spaces - Buthinah A. Bin Dehaish; Rawan K. Alharbi (Journal of Function Spaces)
The present paper seeks to illustrate approximation theorems to the fixed point for generalized α-nonexpansive mapping with the Mann iteration process. Furthermore, the same results are established with the Ishikawa iteration process in the uniformly convex Banach space setting. The presented results expand and refine many of the recently reported results in the literature.